NLRP3 inflammasome inhibition protects against intracranial aneurysm rupture and alters the phenotype of infiltrating macrophages - Dodd, William S.; Patel, Devan; Motwani, Kartik; Lucke-Wold, Brandon; Hosaka, Koji; Hoh, Brian L. (Frontiers in Stroke, 2023)
Background: Aneurysmal subarachnoid hemorrhage is a devastating cerebrovascular disease associated with high morbidity and mortality. Macrophage-mediated mural inflammation is a key pathogenic component contributing to aneurysm rupture.To investigate the effect of pharmacological inhibition of the NLRP3 inflammasome on aneurysm rupture.Methods: Cerebral aneurysms were induced in C57BL/6 mice with a combination of hypertension and an intracranial dose of elastase. Mice were treated with either 40mg/kg MCC950 or saline via intraperitoneal injections. Vascular tissue at the circle of Willis was harvested for analysis via immunofluorescent microscopy or qPCR.Results: NLRP3 + cells are more common in aneurysm tissue compared to normal cerebral vasculature. mRNA expression of downstream NLRP3 pathway components caspase-1, IL-1β, and GSDMD is also increased in aneurysm tissue compared to healthy vessels. There was no difference in aneurysm formation rate between MCC950 and vehicle-treated mice, however MCC950 treatment significantly reduced aneurysm rupture rate. There was no difference in systemic blood pressure between groups. MCC950 treatment also extended symptom-free survival of mice after aneurysm induction. Mechanistically, NLRP3 inhibition decreased the phenotype polarization of infiltrating macrophages without affecting the total number of macrophages in the vessel wall. MCC950 treatment also down-regulated expression of the pro-inflammatory NLRP3-CASP1-IL1B/GSDMD pathway within the vascular tissue.Our results indicate that the NLRP3 inflammasome contributes to aneurysm rupture and macrophage polarization within the vessel wall. The NLRP3 pathway is a promising therapeutic target for the development of therapeutics to prevent aneurysmal hemorrhagic stroke.